1990
DOI: 10.1093/oxfordjournals.jbchem.a123057
|View full text |Cite
|
Sign up to set email alerts
|

Purification and Amino Acid Sequence of Basic Protein II, a Lysine-49-Phospholipase A2 with Low Activity, from Trimeresurus flavoviridis Venom1

Abstract: A basic protein (pI 10.3), named basic protein II, was purified to homogeneity from the venom of Trimeresurus flavoviridis (Habu snake) after four chromatographic steps. The amino acid sequence of this protein was determined by sequencing the S-pyridylethylated derivative and its peptides produced by chemical (cyanogen bromide) and enzymatic (chymotrypsin, clostripain, and Staphylococcus aureus V8 protease) cleavages. The protein consisted of 122 amino acid residues and was found to be identical in sequence to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
43
0

Year Published

1994
1994
2018
2018

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 84 publications
(46 citation statements)
references
References 2 publications
(3 reference statements)
1
43
0
Order By: Relevance
“…6,7) Group III PLA 2 s are found in bee venoms 8) and ubiquitous tissues. 9 14,17,18) This accords with their branching patterns, in the phylogenetic tree. 19) Mathematical examination of the nucleotide sequences of their cDNAs and genes has revealed that they evolved via Darwinian-type accelerated evolution, acquiring diverse physiological activities.…”
Section: Structural Characteristics and Evolution Of The Protobothropsupporting
confidence: 66%
See 1 more Smart Citation
“…6,7) Group III PLA 2 s are found in bee venoms 8) and ubiquitous tissues. 9 14,17,18) This accords with their branching patterns, in the phylogenetic tree. 19) Mathematical examination of the nucleotide sequences of their cDNAs and genes has revealed that they evolved via Darwinian-type accelerated evolution, acquiring diverse physiological activities.…”
Section: Structural Characteristics and Evolution Of The Protobothropsupporting
confidence: 66%
“…Then, in order to obtain an entire fragment harboring the P. elegans pancreatic PLA 2 gene and its 5 0 and 3 0 flanking regions, inverted PCRs were conducted against the liver genomic DNAs following the manufacturer's protocol (Toyobo, Osaka) starting from this 486-nt segment with restriction enzymes, Bal I, Bcl I, EcoR I, Nsi I, Pvu II, Sac I, Sph I, and Ssp I (Nippon Gene, Osaka). The primers employed in PCR against internally ligated fragments were PPP1, 5,6,7,10,11,12,16,17,18,19, and 22, which were based on the known sequences of the previously obtained PCR fragments. The position numbers and sequences of the primers are given in Table 1 0 -CAGCTGCTCCGGAGA-GGAATTGTGAN-3 0 , which can anneal to the 3 0 terminal portion of the 3 0 flanking region of the pancreatic PLA 2 gene, were prepared.…”
Section: Methodsmentioning
confidence: 99%
“…According to the above findings, from components of the venom the phospholipase A2 class formed the biggest part and includes the three most abundant proteins of the whole venom: The highest protein content belongs to the acidic PLA2 1 (16.6%) eluting as fraction 22. Secondly, the basic PLA2 BP (10.4%) was identified in fraction 16 but could not clearly be assigned as BPI or BPII, because of their high similarity, which differs only in a N58D exchange as a single mutation [45]. The third protein is PLA-N(O) (7.9%) of fraction 17, which is a PLA-N K121N isoform (Uniprot-ID: S6BAM8) previously documented for the P. flavoviridis population at Okinawa Island [15].…”
Section: Top-down Analysismentioning
confidence: 99%
“…For example, among PLA 2 isozymes of P. flavoviridis (the habu snake), the Asp49 PLA 2 shows phospholipase activity, whereas basic proteins I and II, with potent myotoxicities, show only very weak enzymatic activity. 1,[4][5][6][7] Furthermore, the physiological activities of the enzymes of the MP family of snake venom vary considerably: some induce hypodermic hemorrhage and others trigger apoptotic cell death. 3) Comparisons of the nucleotide sequences of the genes for such snake venom isozymes have revealed a striking feature, that nucleotide substitutions have occurred substantially more in the protein-coding sequences than in the noncoding sequences.…”
mentioning
confidence: 99%